Patients' preferences for anti-osteoporosis drug treatment: a cross-European discrete choice experiment. (6th April 2017) - Hiligsmann, Mickaël; Dellaert, Benedict G.; Dirksen, Carmen D.; Watson, Verity; Bours, Sandrine; Goemaere, Stefan; Reginster, Jean-Yves; Roux, Christian; McGowan, Bernie; Silke, Carmel; Whelan, Bryan; Diez-Perez, Adolfo; et al.
Abstract: Objectives. To estimate the preferences of osteoporotic patients for medication attributes, and analyse data from seven European countries. Methods. A discrete choice experiment was conducted in Belgium, France, Ireland, the Netherlands, Spain, Switzerland and the UK. Patients were asked to choose repeatedly between two hypothetical unlabelled drug treatments (and an opt-out option) that varied with respect to four attributes: efficacy in reducing the risk of fracture, type of potential common side effects, and mode and frequency of administration. In those countries in which patients contribute to the cost of their treatment directly, a fifth attribute was added: out-of-pocket cost. A mixed logit panel model was used to estimate patients' preferences. Results. In total, 1124 patients completed the experiment, with a sample of between 98 and 257 patients per country. In all countries, patients preferred treatment with higher effectiveness, and 6-monthly subcutaneous injection was always preferred over weekly oral tablets. In five countries, patients also preferred a monthly oral tablet and yearly i.v. injections over weekly oral tablets. In the three countries where the out-of-pocket cost was included as an attribute, lower costs significantly contributed to the treatment preference. Between countries, there were statistically significant differences for 13 out of 42 attribute/level interactions. Conclusion. We found statistically significant differences in patients' preferences for anti-osteoporosis medications between countries, especially for the mode of administration. Our findings emphasized that international treatment recommendations should allow for local adaptation, and that understanding individual preferences is important if we want to improve the quality of clinical care for patients with osteoporosis.